WOMEN EMPOWERMENT AND RIGHTS IN INDIA - M. Thangam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Among the various issues relating to human rights the issue of women’s rights occupies an important position. It is an established fact that women are the primary victims of any kind of violence which in turn leads to the violation of their rights. It is therefore felt necessary to take certain ameliorative steps in order to improve the subjugated condition of women in the traditionally male dominated society. With this urge a number of women’s rights instruments has been developed both at international and national level. Some of them, at international level, include Declaration on the Elimination of Violence against Women, Convention on the Elimination of All Forms of Discrimination against Women (CEDAW), Convention on the Political Rights of Women, Convention on the Nationality of Married Women, Convention on Consent to Marriage, Minimum Age for Marriage and Registration of Marriages etc. Apart from these the other significant events are establishment of the Commission on the Status of Women, declaration of International Women's Year, observing International Women's Day, World Conference of the International Women's Year in Mexico City, declaration of the United Nations Decade for Women, World Conferences in Copenhagen, Nairobi, Beijing and New York etc. This paper intends to analyse the role of women commission and policy enactments in protecting the rights of women in India.